2010
DOI: 10.4088/jcp.09m05504yel
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Prefrontal Function With Pharmacotherapy on a Response Inhibition Task in Adolescent Bipolar Disorder

Abstract: Objective-The aim of the current study is to determine whether pharmacotherapy normalizes cognitive circuitry function supporting voluntary behavioral inhibition in adolescent bipolar disorder (ABD).Method-Healthy controls (HC) and unmedicated patients with ABD in manic, mixed or hypomanic episodes are matched on demographics and IQ (n=13 per group; Mean age=14.4 ±2.4 years). fMRI studies are performed at baseline and after 14 weeks, during which time patients with ABD are treated initially with second generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 38 publications
7
70
1
1
Order By: Relevance
“…Our results of no behavioral difference in depressed group relative to HC, but abnormal neural activity underlying cognitive control in cortical (lateral prefrontal for executing inhibitory control processes and temporal for attentional processing) and subcortical (hippocampus [Fusar-Poli et al 2009], an important region for emotion processing in addition to memory encoding, retention, and retrieval; and thalamus [Li et al 2008], a major relay center that sends inhibitory signals to striatum and motor cortex to stop prepotent responses) are similar to the majority of available studies in non-depressed BD adolescents (Blumberg et al 2003;Chang et al 2004;Leibenluft et al 2007;Passarotti et al 2010;Pavuluri et al 2010;Singh et al 2010). In addition, increased activity of cortical and/or subcortical regions during response inhibition (e.g., no go condition) in this study in BDd relative to HC was similar to the studies in adolescents with nondepressed BD (Blumberg et al 2003;Chang et al 2004;Singh et al 2010).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our results of no behavioral difference in depressed group relative to HC, but abnormal neural activity underlying cognitive control in cortical (lateral prefrontal for executing inhibitory control processes and temporal for attentional processing) and subcortical (hippocampus [Fusar-Poli et al 2009], an important region for emotion processing in addition to memory encoding, retention, and retrieval; and thalamus [Li et al 2008], a major relay center that sends inhibitory signals to striatum and motor cortex to stop prepotent responses) are similar to the majority of available studies in non-depressed BD adolescents (Blumberg et al 2003;Chang et al 2004;Leibenluft et al 2007;Passarotti et al 2010;Pavuluri et al 2010;Singh et al 2010). In addition, increased activity of cortical and/or subcortical regions during response inhibition (e.g., no go condition) in this study in BDd relative to HC was similar to the studies in adolescents with nondepressed BD (Blumberg et al 2003;Chang et al 2004;Singh et al 2010).…”
Section: Discussionmentioning
confidence: 69%
“…Available studies report significant neurocognitive deficits (e.g., response inhibition, attention, working memory) (Pavuluri et al 2006a,b;Joseph et al 2008) and abnormal prefrontal and subcortical activity in response to cognitive control tasks in adolescents with non-depressed BD (Blumberg et al 2003;Chang et al 2004;Leibenluft et al 2007;Passarotti et al 2010;Pavuluri et al 2010;Singh et al 2010). Findings in adults with BD suggest that the depressed state may manifest different cognitive control deficits than do euthymic and hypomanic states (Malhi et al 2007); however, no study has investigated neural correlates of cognitive control in BDd adolescents before and after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the illness-related deficits, treatment effect also has been revealed. For example, Pavuluri et al (69) found that secondgeneration antipsychotics showed enhanced prefrontal and temporal lobe activity in patients with adolescent BD. These deficits have promise as potential biomarkers in the clinical diagnosis of and treatment planning for BD (70).…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…[41] Psikiyatride Güncel Yaklaşımlar -Current Approaches in Psychiatry İleriye dönük klinik çalışmalardaki fMRG sonuçlarına göre, bazı çalışma-larda prefrontal korteks ve temporal bölgelerdeki değişiklikler lamatrojin tedavisi ile normalleşmiştir. [42][43][44] Diğer uzunlamasına çalışmalarda amigdala ve prefrontal korteksteki değişiklikler ile klinik iyileşme arasında korelasyon bulunmuştur. [45,46] Fakat bu değişiklikler üzerinde tedavinin mi genel klinik iyileşmenin mi etkisi olduğu kesin değildir.…”
Section: Tedavinin Nöroradyolojik Bulguları üZerindeki Etkisiunclassified